Reforma legal el art. innumerado 10 (135) literal a), del Código De La Niñez Y Adolescencia, dado el evento de existir negativa por parte del accionado, a someterse a las pruebas científicas del ADN que el Juez/a ordene - Jiménez Jaya, Myriam Judit (2016)
The development of this prequalification as a lawyer revolves around the derivative problems of procedural act of declaration of paternity investigation, where the defendant or respondent has not attended the practice of DNA (deoxyribonucleic acid), evidence. This research aims to conduct a thorough legal, doctrinal and critical analysis of the declaration of paternity, where the defendant or respondent has not attended the practice of DNA (deoxyribonucleic acid), evidence, procedure violates the principle of the right to defense, since the driven is unable to exercise any subsequent claim, this diminishing the basic guarantees of the right to self-defense, which shall be exercisable at any part of the process expeditiously. Furthermore, the development of research I present the stipulations of the laws of other countries, because of its proximity, are influential to our own rules, and which some circumstances be considered to be successful in formulating the proposed reform will be taken. Finally, this work is corroborated by conducting a field study regarding the problem to investigate, to what has been obtained the judgment of a group of professionals in the legal sciences through technical survey and interview who have expressed their views and opinions regarding the proposed theme, suggesting incorporate legal reform to Article 135 paragraph A) of the Code for Children and Adolescents, which is contemplated to a second remark, that the driven can go to comply with the diligence of sampling patterns of DNA (deoxyribonucleic acid).